Two new species of Didicrum Enderlein (Diptera, Psychodidae, Psychodinae) from Argentinean Patagonia - Omad, Guillermo (Zootaxa, 2014)
Two new species of Didicrum from Argentina are described and illustrated: Didicrum naimae and Didicrum letitiae, based on male and female specimens. Specimens were collected with Malaise traps located in Nahuel Huapi National Park, Patagonian region. Including the two new species of Didicrum, twelve are described from South America.